1994 IEEE GLOBECOM. Communications: The Global Bridge
DOI: 10.1109/glocom.1994.512703
|View full text |Cite
|
Sign up to set email alerts
|

Bandwidth allocation based on real time calculations using the convolution approach

Abstract: This paper focusses on one of the methods for bandwidth allocation in an ATM network: the convolution approach. The convolution approach permits an accurate study of the system load in statistical terms by accumulated calculations, since probabilistic results of the bandwidth allocation can be obtained. Nevertheless, the convolution approach has a high cost in terms of calculation and storage requirements. This aspect makes real-time calculations difficult, so many authors do not consider this approach. With t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…In [6] we propose the New Convolution Approach to calculate the bandwidth required by dlfferent traf€ic types to achieve a certain QOS. When using this results, an iterative algorithm determines the sufficient and minimum capacity of a VP so that all the individual QOS are satisfied whenever different traflic classes are multiplexed together on the VP.…”
Section: Pathmentioning
confidence: 99%
“…In [6] we propose the New Convolution Approach to calculate the bandwidth required by dlfferent traf€ic types to achieve a certain QOS. When using this results, an iterative algorithm determines the sufficient and minimum capacity of a VP so that all the individual QOS are satisfied whenever different traflic classes are multiplexed together on the VP.…”
Section: Pathmentioning
confidence: 99%
“…Now, it can be observed that N(t) = f (t, t , t3 t If n calls have arrived and each has the probability p of It can be noted that F(n+I) is the convolution [20] of F(n) and independently not completing by time t, then a sequence of F. Assuming f be the density function of F, it can be n Bernoulli [17] trials is obtained. Thus, …”
mentioning
confidence: 99%